Pedagogical Integration of Traffic Parks: Contextual Learning Resources for Early Childhood Education - Fachrul Rozie; Evie Palenewen; Effendi Limbong; Gisela Silvania Algazira; Zerliyana Luthfiyawati Fazry; Zulkarnain Ramli (Atfaluna: Journal of Islamic Early Childhood Education, 2026)
Purpose – This study investigates how the Karang Anyar Traffic Park in Samarinda, Indonesia, can be integrated pedagogically as a contextual learning resource in Early Childhood Education (ECE). It addresses the gap between public Child-Friendly City policies and the actual pedagogical utilization of specific thematic urban spaces to foster safety awareness and self-regulation in early childhood. Design/methods/approach – A qualitative case study design was employed. Data were collected over a three-month period (August–October 2024) through multi-perspective interviews with a village head, park managers, ECE principals, and teachers, alongside field observations and institutional documentation. The data were analyzed using Braun & Clarke’s thematic analysis framework. Findings – The thematic analysis yielded five interconnected themes demonstrating that the traffic park serves as an effective "third teacher". It facilitates experiential, play-based learning regarding traffic safety and social self-regulation. However, full integration is currently constrained by structural challenges, including unpredictable weather, varying teacher experiences in outdoor pedagogy, and administrative budget limitations for regular park maintenance. Research implications/limitations – The findings are limited by the study's single-site focus, a small participant pool, and a restricted three-month timeframe. Furthermore, this study relies strictly on adult stakeholder perspectives and does not directly incorporate the lived experiences or direct voices of the child participants. Practical implications – This research offers actionable insights for urban planners and educational policymakers to cross-integrate ECE curricula (such as the Merdeka Curriculum) with public infrastructure. It emphasizes the necessity of multi-stakeholder collaboration to sustain public thematic spaces as accessible, safe, and structured learning environments. Originality/value – This study provides empirical evidence on the intentional pedagogical adaptation of thematic public spaces in an Indonesian urban context. It shifts the focus from conventional natural parks to specialized community-based thematic infrastructure for early childhood development.